Fermented Cassava Residue Meal Improves Meat Quality by Regulating Muscle Fiber and Enhancing Lipid Metabolism in Huanjiang Mini-Pigs - Huijiao Jiang; Md. Abul Kalam Azad; Qian Zhu; Hengjia Ni; Xiangfeng Kong (Animals)
This research investigated the effects of cassava residue meal (CRM) and fermented CRM (FCRM) on the growth performance, serum lipid indicators, carcass traits, and meat quality of Huanjiang mini-pigs. One hundred twenty Huanjiang mini-pigs with similar BW (body weight, 8.85 ± 0.64 kg) were divided into three dietary treatment groups: the CON group with a basal diet; the CRM group with a diet containing 5% CRM; and the FCRM group with a diet containing 5% FCRM. The feeding trial was conducted for 30 days. The findings revealed that dietary CRM and FCRM did not influence the growth performance and diarrhea rate of Huanjiang mini-pigs (p > 0.05). Dietary FCRM supplementation increased serum total cholesterol level compared to the CON group while decreasing serum cholinesterase level compared to the CON and CRM groups (p < 0.05). The level of serum low-density lipoprotein-cholesterol was higher (p < 0.05) in the CRM and FCRM groups in regard to the CON group. In addition, CRM and FCRM supplementation reduced (p < 0.05) the backfat thickness and carcass yield of Huanjiang mini-pigs. The meat quality analysis showed that dietary CRM and FCRM improved the meat quality by increasing the intramuscular fat content and redness (a*) value and decreasing the lightness (L*) value. Moreover, the MyHC-IIx expression in the longissimus thoracis (LT) muscle was upregulated (p < 0.05) in the CRM group, while MYHC-IIb expression displayed an increasing trend (p = 0.076) in the FCRM group relative to the CON group. The fatty acid composition in the LT muscle also revealed that the C20:0 level was lower in the CRM and FCRM groups, while the ∑SFA and ∑SFA/∑UFA were reduced (p < 0.05) in the FCRM group relative to the CON group. In summary, dietary CRM and FCRM supplementation improved the meat quality of Huanjiang mini-pigs without affecting growth performance and diarrhea rate. Notably, FCRM exhibited better effects on meat quality than CRM.